Conceptualizing the relationship between course management, learning styles and University students’ academic challenges in China - Chongchong Yang; Soon Singh Bikar Singh (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
Improving the quality of higher education has become the main task of the reform and development of higher education. The pressure of students' study is increasing day by day, and the competition is becoming increasingly fierce. course management and students' learning styles in colleges and universities are all important indicators that affect students' academic challenges. Therefore, this paper investigates the relationship between current university course management, learning styles and students' academic challenges, conducts theoretical research and literature review, summarizes the current actual situation of students' academic challenges and course management, and proposes targeted improvement methods and suggestions for education management in order to further discover the problems. It provides reference for more effective education policy and implementation, and more targeted support measures.